MODELING OF A SPRING-FRICTION ENERGY-ABSORBING DEVICE FOR A FREIGHT CAR - Shokuchkorov Kurbannazar Salim ugli; Kodirjonov Hasan Nodirjon ugli; Kodirjonov Husan Nodirjon ugli (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Energy-absorbing devices are designed to dissipate impact energy, thereby reducing the longitudinal tensile and compressive forces transmitted to the wagon frame through the coupler. In operational practice, the most common units are hexagonal spring-friction devices of types Sh-1-TM, Sh-2-V, Sh-6-TO-4 and others because of their simplicity and the possibility of designing them with satisfactory parameters.